Los mecanismos de la interpretación: la eficacia de la ficción en la reconstrucción de la memoria a propósito de Los girasoles ciegos - de la Paz Cepedello Moreno, María (Studia Romanica Posnaniensia, 2017)
The aim of this paper is to demonstrate the important role that fiction can play in the reconstruction of historical memory. We start from some concepts proposed by phenomenology, and those wisely used by the literary pragmatics and aesthetics of reception, in order to explain the effect that fiction has on the reader regardless of contents or themes. The choice of Los girasoles ciegos is to illustrate the effectiveness of fictional stories in the reconstruction of historical memory through the use of four stories present suitable formal features. These stories allow the reader to interpret the text as own experience.